Intermediate input markets, ICT and innovation in Germany: A firm level analysis - Daniel Cerquera; Gordon J. Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper studies the impact of the adoption of ICT on the economic performance at the firm level, considering explicitly the interaction of adopting firms within the intermediate input market in Germany. The paper identifies and quantifies the importance of adoption externalities and knowledge spillovers inherent in the introduction of ICT. The results show that the adoption of ICT at the firm level is positively affected by the use of ICT downstream and upstream (i.e. by a firm's clients and suppliers). Moreover, the use of ICT upstream(i.e. by a firm's suppliers) negatively affects the extend of IT outsourcing at the firm level, suggesting a substitution effect between inputs provided by suppliers with an intense use of ICT and a firm's demand for external IT services. The paper also finds that the use of ICT within the intermediate input markets positively affects the efficiency of internal processes by increasing the cost reductions generated by the introduction of process innovations.
urn:nbn:de:bsz:180-madoc-332528
Keywords: D22; L25; O32; 330; Information and Communication Technologies; General Purpose Technologies; Intermediate Input Markets; Innovation; Firm Level Data